2017
DOI: 10.1111/coa.12976
|View full text |Cite
|
Sign up to set email alerts
|

One hundred twenty‐five fat myringoplasties: Does marginal perforation matter?

Abstract: Otol Neurotol. 2014;35:1755-1758. Migirov L, Shapira Y, Wolf M. The feasibility of endoscopic transcanal approach for insertion of various cochlear electrodes: a pilot study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…However, in a recent study that analysed the orientation of the cochlear basal turn in relation to the ear canal, it was demonstrated that the trajectory provided by the conventional posterior tympanotomy aligned more favourably with the cochlear basal turn than the transcanal approach, thus may result in less damage caused by deflection of the electrode array in the scala tympani. 10 In addition, it has also been reported that transcanal…”
Section: Comparisons With Other Studiesmentioning
confidence: 95%
“…However, in a recent study that analysed the orientation of the cochlear basal turn in relation to the ear canal, it was demonstrated that the trajectory provided by the conventional posterior tympanotomy aligned more favourably with the cochlear basal turn than the transcanal approach, thus may result in less damage caused by deflection of the electrode array in the scala tympani. 10 In addition, it has also been reported that transcanal…”
Section: Comparisons With Other Studiesmentioning
confidence: 95%
“…11,[20][21][22][23] Many researchers have demonstrated appropriate indications or conditions for fat myringoplasty. 1,3,10,21) We summarize 2 sets of representative criteria. First, Fiorino and Barbieri 1) suggested that 1) the interval since a previous surgery should be ≥6 months; 2) perforation of the pars tensa should be no larger than 5 mm; 3) there should be non-marginal localization, i.e., involving the annulus or exposing the malleus handle; 4) there should be no calcific plaques or atrophic areas adjacent to the perforation; 5) the mucous layer in the tympanic cavity should appear normal; 6) there should be no acute inflammation; 7) no middle ear discharge in the last 3 months; 8) no evidence of cholesteatoma; 9) no planned ossicular reconstruction; 10) and no major eustachian tube dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Second, Malafronte and Filosa. 10) proposed the following criteria: 1) absence of granulomatous tissue and cholesteatoma, 2) absence of ossicular chain interruption, and 3) perforation size of up to 35% of the eardrum surface. We believe that although these criteria are not absolute guidelines, they suggest good surgical conditions for fat myringoplasty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations